2010
DOI: 10.5194/acp-10-1689-2010
|View full text |Cite
|
Sign up to set email alerts
|

Recent increase in aerosol loading over the Australian arid zone

Abstract: Abstract. Collocated sun photometer and nephelometer measurements at Tinga Tingana in the Australian Outback over the decade

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(64 citation statements)
references
References 35 publications
5
59
0
Order By: Relevance
“…As a consequence, it is the major source of dust from the Australian continent. Mitchell et al (2010) noted an increase in aerosol loading over Australia's arid interior during the decade 1997-2007, presumably a result of the recent prolonged drought. Greene et al (2009) developed a conceptual model that describes the various dust sources and sinks, and the modes of transport of dust materials both into and out of source areas in SE Australia.…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, it is the major source of dust from the Australian continent. Mitchell et al (2010) noted an increase in aerosol loading over Australia's arid interior during the decade 1997-2007, presumably a result of the recent prolonged drought. Greene et al (2009) developed a conceptual model that describes the various dust sources and sinks, and the modes of transport of dust materials both into and out of source areas in SE Australia.…”
Section: Introductionmentioning
confidence: 99%
“…Leys et al, 2008;Bullard et al, 2008) but less so via sun photometry, where the measurand -column aerosol optical depth -is the required input for climate and remote sensing studies. However, Mitchell et al (2010) analysed sun photometer and nephelometer measurements from Tinga Tingana in the Australian arid zone during the Millennium Drought (2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010) and found an approximate doubling in both column and near-surface aerosol during the austral summer over the duration of the drought. Feedbacks related to dust aerosol were modelled by Rotstayn et al (2011), who found that inclusion of interactive dust in the model amplifies the impact of the El Niño-Southern Oscillation cycle on Australian climate.…”
Section: Introductionmentioning
confidence: 99%
“…A 10-year aerosol climatology at this site (Mitchell et al, 2010) showed dual peaks in AOD in September and January, the former including a significant fine-particle mode characteristic of smoke from long-range transport, while the January peak was dominated by coarse particles characteristic of wind-blown dust. Figure 3 compares the observed and modelled annual cycles of AOD.…”
Section: Dust Simulationmentioning
confidence: 99%
“…Satellite retrievals identify the large (1 140 000 km 2 ) Lake Eyre Basin of central-eastern Australia as the largest dust source in the Southern Hemisphere (Prospero et al, 2002); see also Washington et al (2003), McTainsh et al (2007), Bullard et al (2008) and Mitchell et al (2010). Compared to the major Northern Hemisphere dust source regions, Australian average dust emissions are relatively low.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation